The migration of bisphenols from beverage cans and reusable sports bottles. (30th November 2020) - Kovačič, Ana; Gys, Celine; Gulin, Martin Rafael; Kosjek, Tina; Heath, David; Covaci, Adrian; Heath, Ester
Highlights: A sensitive and accurate GC–MS/MS method for 12 BPs was developed and validated. BPs are stable in dried (8 weeks, −20 °C) and derivatised extracts (7 days, 21 °C for). Cans and steel bottles leached the highest concentrations of BPA (< SML) and BPF. Simulant C is more aggressive than simulant B. New insights into BPs migration from FCM that can lower the risk to consumer health. Abstract: A precise and accurate GC–MS/MS method with ng L −1 LLOQs, acceptable recovery (78–107%) and estimated uncertainty (U > 20%, except at LLOQ) was developed following the Eurachem guidelines. We established the migration and stability of twelve bisphenols in two food simulants (C: 20% ethanol, and B: 3% acetic acid) from beverage cans (n = 16) and reusable metal and plastic sports bottles (n = 51). Bisphenols were stable in dried (eight weeks, −20 °C) and derivatised extracts (seven days, 21 °C). Cans leached BPA (<5865 ng L −1 ), three BPF isomers (8.2–1286 ng L −1 ) and BPAP (1.6 ng L −1 ), while bottles leached BPA (<222 ng L −1 ) and BPF, BPE, BPB and BPZ (1.1–4.6 ng L −1 ). Simulant C was more aggressive than simulant B, and concentrations of bisphenols decreased with consecutive exposure to simulants. Levels of BPA migrating from cans did not exceed the specific migration limits.